Fiber early-strength composite concrete and preparation method thereof

CN123003235APending Publication Date: 2026-10-30JIANGSU MODERN ROAD & BRIDGE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611367696.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-04
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

但是,如果把它单独用作高速公路桥梁伸缩缝的修补材料,还存在一些不足

Benefits of technology

该纤维早强复合混凝土及其制备方法中,将高强改性硫铝酸盐水泥与粉煤灰硅酸盐水泥混合使用,既保证了混凝土的早期强度,又维持了后期强度的持续增长。加入减水剂降低了需水量,改善了流动性和密实度;加入缓凝剂延缓了初期的水化反应,降低了放热峰值,延长了凝结时间,避免了早期水化过快导致的收缩和微裂缝,实现了强度提升与防止开裂的平衡。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123003235A_ABST
    Figure CN123003235A_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of new pavement material, in particular to a kind of fiber early-strength composite concrete and its preparation method.The raw materials in each cubic meter of pouring material, content ratio are as follows: fly ash portland cement: 100kg-350kg;High-strength modified sulphoaluminate cement: 250kg-600kg;Coarse aggregate: 805kg-1055kg;Fine aggregate: 650kg-850kg;Water: 140kg-170kg;Steel fiber: 20kg-40kg;Polyvinyl alcohol fiber: 20kg-40kg;Sodium gluconate (retarder): 0.3%-0.5% of cement quality;Polycarboxylic acid (water reducing agent): 0.1%-0.4% of cement quality;Early strength agent: 0.1%-0.3% of cement quality.The present application can meet the requirements of rapid opening traffic, high early strength, not easy to produce cracks and good durability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of new road surface materials technology, specifically to a fiber-reinforced early-strength composite concrete and its preparation method. Background Technology

[0002] Expansion joints are crucial for ensuring the safety and lifespan of bridges. They release the deformation stress caused by temperature changes, material shrinkage, and vehicle traffic, preventing damage to the main bridge structure while ensuring a smooth bridge deck and waterproof sealing. In actual bridge use, expansion joints frequently fail, primarily due to two factors: first, the direct impact and repeated crushing by passing vehicles, especially heavy vehicles, leading to material fatigue, deformation, and even fracture; second, external environmental influences such as ultraviolet radiation, rainwater, de-icing salt, and temperature changes, causing rubber to harden and crack, metal to rust, seals to fail, and debris to clog. These problems ultimately render the expansion joints ineffective, leading to safety hazards such as vehicle bouncing and leaks.

[0003] High-strength modified sulfoaluminate cement is frequently used in road repair due to its advantages such as rapid hardening, high early strength, and good frost and water resistance. However, its use as a standalone repair material for highway bridge expansion joints has some drawbacks. Firstly, the raw material cost of this cement is relatively high. Secondly, its hydration reaction upon contact with water is extremely rapid, releasing a large amount of heat. This causes a rapid rise in internal temperature and heat concentration at the repair site in the early stages, significantly increasing the difficulty of on-site construction and maintenance. Furthermore, this intense heating reaction easily leads to cracks due to excessive temperature changes and material shrinkage, making it difficult to meet the stringent requirements for volume stability and crack resistance in expansion joint areas.

[0004] Therefore, current engineering practices require the development of a concrete repair material for highway bridge expansion joints that has high early strength, low construction and maintenance difficulty, is not prone to cracking, and is reasonably priced. Summary of the Invention

[0005] The purpose of this invention is to provide a fiber-reinforced early-strength composite concrete and its preparation method to solve the problems mentioned in the background art.

[0006] To achieve the above objectives, the present invention provides a fiber-reinforced early-strength composite concrete, wherein the raw materials and their proportions per cubic meter of composite concrete are as follows: Fly ash silicate cement: 100kg-350kg; High-strength modified sulfoaluminate cement: 250kg-600kg; Coarse aggregate: 805kg-1055kg; Fine aggregate: 650kg-850kg; Water: 140kg-170kg; Steel fiber: 20kg-40kg; Polyvinyl alcohol fiber: 20kg-40kg; Sodium gluconate retarder: 0.3%-0.5% of the total mass of fly ash silicate cement and high-strength modified sulfoaluminate cement; Polycarboxylate superplasticizer: accounting for 0.1%-0.4% of the total mass of fly ash silicate cement and high-strength modified sulfoaluminate cement; Early strength agent: accounting for 0.1%-0.3% of the total mass of fly ash silicate cement and high-strength modified sulfoaluminate cement.

[0007] In this invention, high-strength modified sulfoaluminate cement rapidly forms a crystalline skeleton upon contact with water, providing early strength support for the concrete. Fly ash silicate cement undergoes a continuous hydration reaction in the later stages, generating a stable gel structure, compensating for the limitations of single cement in early strength development, thus ensuring good strength in both the early and later stages of concrete development. Coarse and fine aggregates are mixed in a specific ratio; the coarse aggregate forms the skeleton to resist deformation, while the fine aggregate fills the voids, enhancing overall volume stability. An appropriate amount of water ensures thorough dispersion of cement particles. Steel fibers are interspersed throughout the concrete, enhancing crack and impact resistance through physical anchoring; polyvinyl alcohol fibers fill small pores, inhibiting shrinkage during the incomplete hardening stage and improving impermeability. Sodium gluconate retarder coats the surface of cement particles, delaying the initial hydration reaction and ensuring workability during construction; polycarboxylate superplasticizer releases water, improving the fluidity of the paste. The combined effects of these raw materials ultimately result in concrete that is characterized by rapid hardening, high early strength, resistance to cracking, and long-term stability.

[0008] Furthermore, the high-strength modified sulfoaluminate cement is prepared by the following steps: mixing limestone, bauxite, gypsum and a modifier, and then ultra-fine grinding to a specific surface area > 450 m². 2 After being fed into the kiln, the clinker is calcined at a constant temperature of 1280℃-1380℃ to form clinker mainly composed of anhydrous calcium sulfoaluminate. The clinker is then rapidly cooled immediately after exiting the kiln and ground together with an appropriate amount of gypsum to produce finished cement.

[0009] Furthermore, the water-reducing agent used is a polycarboxylate water-reducing agent.

[0010] Polycarboxylic acid molecules adsorb onto the surface of cement particles, giving the particles a negative charge and generating electrostatic repulsion. At the same time, their molecular chains create spatial barriers between particles, preventing particle aggregation, thereby dispersing cement particles, improving fluidity, and regulating the hydration rate.

[0011] Furthermore, the retarder used is sodium gluconate retarder.

[0012] Sodium gluconate adsorbs onto the surface of cement particles, forming a barrier layer that prevents moisture from contacting the minerals. Simultaneously, it binds to calcium ions that initially dissolve, reducing the concentration of free calcium ions. This effect slows down the precipitation rate of hydration products, effectively inhibiting the hydration reaction process and achieving a retarding effect, especially noticeable for rapidly reacting sulfoaluminate minerals.

[0013] Furthermore, the steel fiber used is a hook-shaped steel fiber with a length of 30mm.

[0014] The hook-shaped steel fibers are fixed in the cement matrix through the hook structure at both ends. When the concrete develops tiny cracks due to shrinkage or stress, the hooks of the fibers physically connect the two sides of the crack and bear the tensile force, delaying the crack from enlarging. At the same time, the randomly distributed fiber network increases the bond strength between the fibers and the matrix, disperses concentrated stress, and reduces early shrinkage of the concrete, thereby improving the crack resistance and impact resistance of the concrete.

[0015] Furthermore, the polyvinyl alcohol fiber used is a 12mm spiral polyvinyl alcohol fiber.

[0016] The grooves on the surface of the spiral polyvinyl alcohol fiber increase the contact area and friction with the cement matrix, fixing it in the matrix like a micro-anchor, thereby dispersing shrinkage stress. When the concrete is not fully hardened, the fiber reduces water seepage and aggregate settling, minimizing early shrinkage cracks. After hardening, the fiber bonds tightly to the matrix, and when micro-cracks appear, the fiber can withstand tensile forces, delaying crack propagation. Furthermore, the fiber can combine with cement hydration products, improving the material's density and impermeability.

[0017] In another aspect, the present invention provides a method for preparing the above-mentioned fiber-reinforced early-strength composite concrete, comprising the following steps: dry mixing high-strength modified sulfoaluminate cement and fly ash silicate cement for 1.5-2 minutes, then adding steel fibers, polyvinyl alcohol fibers, coarse aggregates, and fine aggregates and dry mixing for 1.5-2 minutes; pouring polycarboxylate superplasticizer, sodium gluconate retarder, and early-strength agent into water and stirring until completely dissolved in water; then pouring water into the cement mixture and wet mixing for 2-4 minutes until the concrete mixture has good fluidity.

[0018] The above preparation method is simple, the raw material cost is controllable, and it can produce concrete with good workability, stable hydration process, and good early strength, late strength and crack resistance.

[0019] Compared with the prior art, the beneficial effects of the present invention are as follows: In this fiber-reinforced early-strength composite concrete and its preparation method, high-strength modified sulfoaluminate cement and fly ash silicate cement are mixed, which ensures both the early strength of the concrete and the continuous growth of its later strength. The addition of a water-reducing agent reduces water demand and improves fluidity and density; the addition of a retarder slows down the initial hydration reaction, reduces the exothermic peak, and prolongs the setting time, avoiding shrinkage and micro-cracks caused by excessively rapid early hydration, thus achieving a balance between strength enhancement and crack prevention.

[0020] This invention uses both steel fibers and polyvinyl alcohol fibers. The hook structure of the steel fibers can effectively inhibit the enlargement of cracks, while the polyvinyl alcohol fibers can block the generation of micro-cracks. Together, they improve the crack resistance of concrete. Attached Figure Description

[0021] Figure 1 This is an overall flowchart of an embodiment of the present invention. Detailed Implementation

[0022] The technical solutions in the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0023] In these embodiments, all operations without specifically specified experimental conditions are assumed to be performed using conventional technical conditions in the field or standard methods recommended by relevant instrument manufacturers. Unless otherwise specified, the materials and experimental instruments mentioned are commercially available products conforming to national standards or industry-standard specifications, and can be directly purchased through open market channels.

[0024] The steel fiber was purchased from Hunan Huitong New Material Co., Ltd., with a tensile strength ≥600MPa; the polyvinyl alcohol fiber was purchased from Anhui Wanwei Group Co., Ltd., with a tensile strength ≥450MPa; the sodium gluconate retarder and polycarboxylate superplasticizer were purchased from Sika (China) Co., Ltd.

[0025] Example 1: A quick-repair concrete refractory for expansion joints of highway bridges, prepared to a depth of 1m. 3 Concrete includes the following steps: Mix 540 kg of high-strength modified sulfoaluminate cement and 60 kg of fly ash silicate cement dry for 1.5-2 minutes; then add 20 kg of steel fiber, 40 kg of polyvinyl alcohol fiber, 1055 kg of coarse aggregate, and 650 kg of fine aggregate and dry mix for 1.5-2 minutes; pour 1.8 kg of water-reducing agent, 3 kg of retarder, and 0.6 kg of early-strength agent into 170 kg of water and stir until completely dissolved; then pour the water containing the admixture into the cement mixture and wet mix for 2-4 minutes, pour the concrete and vibrate it to form the shape, sprinkle water every 15 minutes for curing, and cure for 1 hour.

[0026] Example 2: A quick-repair concrete slurry for expansion joints of highway bridges, prepared to a depth of 1m. 3 Concrete includes the following steps: Mix 480 kg of high-strength modified sulfoaluminate cement and 120 kg of fly ash silicate cement dry for 1.5-2 minutes; then add 20 kg of steel fiber, 40 kg of polyvinyl alcohol fiber, 1055 kg of coarse aggregate, and 650 kg of fine aggregate and dry mix for 1.5-2 minutes; pour 1.8 kg of water-reducing agent, 3 kg of retarder, and 0.6 kg of early-strength agent into 140 kg of water and stir until completely dissolved; then pour the water containing the admixture into the cement mixture and wet mix for 2-4 minutes, pour the concrete and vibrate it to form the shape, sprinkle water every 15 minutes for curing, and cure for 1 hour.

[0027] Example 3: A quick-repair concrete refractory for expansion joints of highway bridges, prepared to a depth of 1m. 3 Concrete includes the following steps: Mix 540 kg of high-strength modified sulfoaluminate cement and 60 kg of fly ash silicate cement dry for 1.5-2 minutes; then add 20 kg of steel fiber, 40 kg of polyvinyl alcohol fiber, 805 kg of coarse aggregate, and 850 kg of fine aggregate and dry mix for 1.5-2 minutes; pour 1.8 kg of water-reducing agent, 3 kg of retarder, and 0.6 kg of early-strength agent into 140 kg of water and stir until completely dissolved; then pour the water containing the admixture into the cement mixture and wet mix for 2-4 minutes, pour the concrete and vibrate it to form the shape, sprinkle water every 15 minutes for curing, and cure for 1 hour.

[0028] Example 4: A quick-repair concrete refractory for expansion joints of highway bridges, prepared to a depth of 1m. 3 Concrete includes the following steps: Mix 540 kg of high-strength modified sulfoaluminate cement and 60 kg of fly ash silicate cement dry for 1.5-2 minutes; then add 30 kg of steel fiber, 30 kg of polyvinyl alcohol fiber, 1055 kg of coarse aggregate, and 650 kg of fine aggregate and dry mix for 1.5-2 minutes; pour 1.8 kg of water-reducing agent, 3 kg of retarder, and 0.6 kg of early-strength agent into 170 kg of water and stir until completely dissolved; then pour the water containing the admixture into the cement mixture and wet mix for 2-4 minutes, pour the concrete and vibrate it to form the shape, sprinkle water every 15 minutes for curing, and cure for 1 hour.

[0029] Example 5: A quick-repair concrete refractory for expansion joints of highway bridges, prepared to a depth of 1m. 3 Concrete includes the following steps: Mix 540 kg of high-strength modified sulfoaluminate cement and 60 kg of fly ash silicate cement dry for 1.5-2 minutes; then add 40 kg of steel fiber, 20 kg of polyvinyl alcohol fiber, 1055 kg of coarse aggregate, and 650 kg of fine aggregate and dry mix for 1.5-2 minutes; pour 1.8 kg of water-reducing agent, 3 kg of retarder, and 0.6 kg of early-strength agent into 170 kg of water and stir until completely dissolved; then pour the water containing the admixture into the cement mixture and wet mix for 2-4 minutes, pour the concrete and vibrate it to form the shape, sprinkle water every 15 minutes for curing, and cure for 1 hour.

[0030] Example 6: A quick-repair concrete refractory for expansion joints of highway bridges, prepared to a depth of 1m. 3 Concrete includes the following steps: Mix 540 kg of high-strength modified sulfoaluminate cement and 60 kg of fly ash silicate cement dry for 1.5-2 minutes; then add 20 kg of steel fiber, 40 kg of polyvinyl alcohol fiber, 1055 kg of coarse aggregate, and 650 kg of fine aggregate and dry mix for 1.5-2 minutes; pour 1.2 kg of water-reducing agent, 1.8 kg of retarder, and 0.6 kg of early-strength agent into 170 kg of water and stir until completely dissolved; then pour the water containing the admixture into the cement mixture and wet mix for 2-4 minutes, pour the concrete and vibrate it to form the shape, sprinkle water every 15 minutes for curing, and cure for 1 hour.

[0031] Example 7: A quick-repair concrete refractory for expansion joints of highway bridges, prepared to a depth of 1m. 3 Concrete includes the following steps: Mix 540 kg of high-strength modified sulfoaluminate cement and 60 kg of fly ash silicate cement dry for 1.5-2 minutes; then add 20 kg of steel fiber, 40 kg of polyvinyl alcohol fiber, 1055 kg of coarse aggregate, and 650 kg of fine aggregate and dry mix for 1.5-2 minutes; pour 2.4 kg of water-reducing agent, 4.2 kg of retarder, and 0.6 kg of early-strength agent into 170 kg of water and stir until completely dissolved; then pour the water containing the admixture into the cement mixture and wet mix for 2-4 minutes, pour the concrete and vibrate it to form the shape, sprinkle water every 15 minutes for curing, and cure for 1 hour.

[0032] Comparative Example 1: A quick-repair concrete pouring material for expansion joints of highway bridges, which differs from Example 1 in that steel fibers and polyvinyl alcohol fibers are not added in this comparative example.

[0033] Comparative Example 2: A quick-repair concrete pouring material for expansion joints of highway bridges, which differs from Example 1 in that no water-reducing agent and retarder are added in this comparative example.

[0034] Comparative Example 3: A quick-repair concrete pouring material for expansion joints of highway bridges. The difference from Example 1 is that the amount of high-strength modified sulfoaluminate cement used in this comparative example is 600 kg, and no fly ash silicate cement is added.

[0035] Test example: The test methods and standards are as follows, and the results are shown in Table 1.

[0036] Compressive strength testing: Standard test blocks were prepared in accordance with GB / T 50081-2019 "Standard for Test Methods of Mechanical Properties of Ordinary Concrete", and the compressive strength of the standard test blocks after curing for 3 hours, 1 day and 7 days was measured.

[0037] Setting time: The setting time of the test blocks was determined in accordance with GB / T 1346-2001 "Standard consistency water requirement, setting time and soundness test method for cement".

[0038] Table 1: Experimental Results

[0039] Combining Examples 1 and 2 with Comparative Example 3, it can be seen that the 1-day and 7-day compressive strengths of Examples 1 and 2 are superior to those of Comparative Example 3. The concrete specimens prepared in Comparative Example 3, due to the absence of fly ash silicate cement, exhibited lower later-stage strength compared to Example 1. This indicates that adding fly ash silicate cement to high-strength modified sulfoaluminate cement can improve the overall performance of early-strength concrete, resulting in materials with not only high early-stage strength but also good later-stage strength.

[0040] Combining Examples 1 and 3, it can be seen that the compressive strength data of Example 1 are better than those of Example 3. This indicates that the ratio of 1055 kg coarse aggregate to 650 kg fine aggregate is better than the ratio of 805 kg coarse aggregate to 850 kg fine aggregate. Appropriately increasing the amount of coarse aggregate helps to improve the compressive strength of concrete.

[0041] As can be seen from Examples 1, 4, and 5 and Comparative Example 1, the compressive strength of Comparative Example 1, which did not contain steel fibers and polyvinyl alcohol fibers, was lower at all stages than that of Examples 1, 4, and 5, which contained both fibers. Furthermore, the concrete surface of Comparative Example 1 showed severe cracking. This demonstrates that the addition of both fibers has a significant effect on improving compressive and crack resistance.

[0042] Combining Examples 1, 6, and 7 with Comparative Example 2, it can be seen that all data from Example 1 are superior to those from Examples 6 and 7, where the admixture dosage was changed. Comparative Example 2, which did not contain water-reducing agents or retarders, had a slightly higher 3-hour compressive strength than Example 1. However, a few cracks appeared on the surface of the concrete in Comparative Example 2. This is because the early hydration reaction of pure sulfoaluminate was too vigorous, resulting in concentrated heat release and shrinkage cracks on the concrete surface. This demonstrates that the appropriate addition of water-reducing agents and retarders can effectively control the reaction rate and prevent cracking.

[0043] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely preferred examples and are not intended to limit the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the present invention as claimed. The scope of protection of the present invention is defined by the appended claims and their equivalents.

Claims

1. A fiber-reinforced early-strength composite concrete, characterized in that, The raw materials and their proportions per cubic meter of composite concrete are as follows: Fly ash silicate cement: 100kg-350kg; High-strength modified sulfoaluminate cement: 250kg-600kg; Coarse aggregate: 805kg-1055kg; Fine aggregate: 650kg-850kg; Water: 140kg-170kg; Steel fiber: 20kg-40kg; Polyvinyl alcohol fiber: 20kg-40kg; Sodium gluconate retarder: 0.3%-0.5% of the total mass of fly ash silicate cement and high-strength modified sulfoaluminate cement; Polycarboxylate superplasticizer: accounting for 0.1%-0.4% of the total mass of fly ash silicate cement and high-strength modified sulfoaluminate cement; Early strength agent: accounting for 0.1%-0.3% of the total mass of fly ash silicate cement and high-strength modified sulfoaluminate cement.

2. The fiber-reinforced early-strength composite concrete according to claim 1, characterized in that, The high-strength modified sulfoaluminate cement is prepared by the following steps: Limestone, bauxite, gypsum, and a modifier are mixed and then ultra-finely ground to a specific surface area > 450 m². 2 After being fed into the kiln, the clinker is calcined at a constant temperature of 1280℃-1380℃ to form clinker mainly composed of anhydrous calcium sulfoaluminate. The clinker is then rapidly cooled immediately after exiting the kiln and ground together with an appropriate amount of gypsum to produce finished cement.

3. The fiber-reinforced early-strength composite concrete according to claim 1, characterized in that, The steel fibers used are 30mm long end-hooked steel fibers.

4. The fiber-reinforced early-strength composite concrete according to claim 1, characterized in that, The polyvinyl alcohol fiber used is a 12mm spiral polyvinyl alcohol fiber.

5. A method for preparing fiber-reinforced early-strength composite concrete as described in any one of claims 1-4, characterized in that, Includes the following steps: Dry mix high-strength modified sulfoaluminate cement and fly ash silicate cement for 1.5-2 minutes; Add steel fiber, polyvinyl alcohol fiber, coarse aggregate, and fine aggregate and dry mix for 1.5-2 minutes; Add the polycarboxylate superplasticizer, sodium gluconate retarder, and early strength agent to water and stir until they are completely dissolved in the water. Then pour the water into the cement mixture and mix for 2-4 minutes.